2021
DOI: 10.19102/icrm.2021.120801
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Outcomes of Cryoballoon Ablation of the Left Atrial Posterior Wall in Conjunction with Pulmonary Vein Isolation

Abstract: There is strong evidence in support of pulmonary vein isolation (PVI) with concomitant left atrial (LA) posterior wall (PW) isolation (PWI) for the treatment of patients with persistent atrial fibrillation (persAF). While this may be achieved using surgical and catheter-based strategies, there is growing interest in performing this approach using the cryoballoon. There are several potential advantages to this strategy. First, lesions created using the current-generation cryoballoons are typically large and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Pulmonary vein isolation alone may be insufficient for treatment of patients with persistent AF. The posterior left atrial region encompassed by the LA roof, superiorly, the left and the right PVs, laterally, and the plane extending from the lower borders of the left and the right inferior PVs, form the PV component of the left atrial posterior wall, which has been implicated in genesis and maintenance of persistent AF (302). Surgical literature has suggested that isolating the "box" between the PVs in the left atrial posterior wall (LAPW) is associated with improved AF outcomes (302).…”
Section: Evolving Concepts In Catheter Ablation Of Afmentioning
confidence: 99%
“…Pulmonary vein isolation alone may be insufficient for treatment of patients with persistent AF. The posterior left atrial region encompassed by the LA roof, superiorly, the left and the right PVs, laterally, and the plane extending from the lower borders of the left and the right inferior PVs, form the PV component of the left atrial posterior wall, which has been implicated in genesis and maintenance of persistent AF (302). Surgical literature has suggested that isolating the "box" between the PVs in the left atrial posterior wall (LAPW) is associated with improved AF outcomes (302).…”
Section: Evolving Concepts In Catheter Ablation Of Afmentioning
confidence: 99%
“…PVI + LAPWI with cryoballoon ablation has demonstrated consistent clinical outcomes, especially in randomized controlled trials [ 15 ]. There are several potential advantages to cryoablation [ 16 ]. First, lesions created using the cryoballoon are often larger.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, cryoballoon ablation offers a simple technique to ablate and debulk the LAPW. Moreover, cryoenergy can be considered safer with regard to anatomical structures that are close to the LAPW (i.e., the esophagus) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The posterior wall and the PVs are derived from the same mediastinal myocardium during embryological development, therefore the propensity for arrhythmogenicity within the posterior wall is not surprising. The cardiomyocytes in the PVs and posterior wall have unique electrophysiological properties related to sodium and calcium contents and potassium currents such that they have short action potentials, reduced resting membrane potentials, and are susceptible to spontaneous depolarizations 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…The cardiomyocytes in the PVs and posterior wall have unique electrophysiological properties related to sodium and calcium contents and potassium currents such that they have short action potentials, reduced resting membrane potentials, and are susceptible to spontaneous depolarizations. [5][6][7] In addition to harboring triggers for inducing AF, the posterior wall can also serve as substrate for perpetuating AF. Heterogenous myocardial fiber orientation with the posterior wall results sets the stage for nonuniform anisotropy, which in turn can lead to conduction abnormalities including local reentry.…”
mentioning
confidence: 99%